The Influence of Compensation and Work Experience on the Performance of ASN Employees at Satpol PP and Firefighters in South Bengkulu Regency - Tanti Harlena; Eska Prima Monique; Siti Hanila (Universitas Dehasen Bengkulu, 2023)
In a governance organization require the quality of human being as labour yielding result of optimal job as according to its job goals. Target of this research To prove Compensation and Job Experience have an effect on to performance officer of ASN in Satpol PP and of Damkar Sub-Province of Bengkulu South.Sampel of part of population as for in this research is entire/all Officer of ASN in Satpol PP and of Damkar Bengkulu south. Researcher take sampel by accidental sampling chosen some one who is assumed can deputize the the population which amount to 42 people officer of ASN. Result of Analysis linear regression of bergaanda the is Equation : Y = 15,435 + 0,464 X1 + 0,176 X2+E, this matter depict direction of regresi which are positive, its meaning of compensation variable ( X1) and Job experience ( X2) there are positive influence to Performance officer ( Y) [in] Satpol PP and of damkar Sub-Province of Bengkulu South.Level of coefficient value of determinasi from result of enumeration by using SPSS can know by coefficient value of determinasi of R square equal to0,570. Matter this means that compensation value ( X1) and job experience value ( X2) have an effect on to officer performance ( Y) equal to 57,0% while the rest 43,0 % influenced by other variable which do not check in research. Result of test of t level of signifikansi 0,05 explaining that by partial job experience and compensation have influence which is signifikan to Performance officer in PP satpol and of Damkar Sub-Province of Bengkulu South. Result of test of f at level of signifikansi 0,05 explaining that compensation , and job experience have influence by simultan signifikan to Performance officer at Satpol PP and of Damkar Sub-Province of Bengkulu South..